Analysis of the sustainable public transportation plans in Poland - Gorzelanczyk, Piotr; Madajczak, Aleksandra (Technical Sciences, 2023)
A sustainable transportation development plan is a strategic document that is created to guarantee convenient conditions in terms of the mobility of users and to ensure all other aspects that aim to improve the quality of life in the city. It is created on the basis of existing planning practices, using documents that already exist in this area and with the participation of various social groups. For this reason, the purpose of this study is to analyze sustainable public transportation development plans for selected 10 municipalities in Poland. The authors will analyze the sustainable development plans of these cities, try to find common features in them, and suggest how a given plan can be expanded to seek better solutions for creating sustainable urban mobility to replace previously developed transportation plans.